Radicalizing Rawls - Chartier, G. author. aut Link
XI, 205 p.
Keywords: This book is a critical examination of John Rawls's account of the normative grounds of international law, arguing that Rawls unjustifiably treats groups - rather than particular persons - as foundational to his model of international justice.